Modelo de determinação da performance relativa em provas de triatlo: uma proposta com base em tamanho de efeito - Pandelo Junior, Domingos Rodrigues [UNIFESP] (2019)
Introduction: Sports practice, especially in high performance, is extremely complex, multifactorial, so the result is decided in detail. In general, the analysis of the performance of an athlete is measured, in individual tests, by their final position in it. In the present study will be presented an alternative proposal able to rank the athletes taking into account their consistency, based on the times obtained and not just their final position. Objective: Establish a relative performance measure that can be used to compare the performance of athletes, contemporaries and / or over time, as well as rank current athletes. Methodology: 24 athletes were selected to compose the sample. The selection criterion was to have figured at least five times in the top 10 in the Ironman World Championship in Hawaii. A model proposal was presented, able to measure the relative performance of athletes, based on the comparison of their performance with the average performance of their competitors, adjusted by the standard deviation of the average performance of the competitors. Results: Based on the proposed model, the overall performance ranking of the 24 selected athletes was calculated, as well as the ranking by modality (swimming, cycling and running) for each of the competitors. Conclusions: A relative performance measure, based on effect size, and considering the performance of each athlete in relation to the average performance of the other competitors, can be an additional instrument to evaluate the relative performance of the athletes, as well as to assist coaches and athletes in search of better performance.